2020
DOI: 10.1111/rec.13018
|View full text |Cite
|
Sign up to set email alerts
|

Endozoochory of a dry‐fruited tree aids quarry passive restoration and seed soaking further increases seedling emergence

Abstract: As practitioners promote passive restoration as a complementary approach to technical reclamation, it is imperative to know its drivers. Although the consequences of endozoochory can be crucial to passive restoration success, few experimental studies assess the use of heavily disturbed sites by seed dispersers such as carnivores and how the seeds they bring in emerge and survive. Using an indoor sowing experiment conducted in a quarry located within a natural park in Portugal, we examined for the first time ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Many wildlife species tend to avoid disturbances associated with roads such as moving vehicles, noise, and light (D'Amico et al, 2015;Denneboom et al, 2021). Although the carnivore species with the most crossings in our work are not particularly intolerant to human presence (Salgueiro et al, 2020), locations farthest from the paved roads are expected to still be areas where they forage and disperse the most across canals throughout their territory, increasing the likelihood of canal encounters and crossings. In the particular case of overpasses on irrigation canals, these generally connect unpaved roads used mainly by agricultural vehicles, implying little disturbance for these animals (Gačić et al, 2013).…”
Section: Primary Drivers Of Canal Crossings Through Overpassesmentioning
confidence: 92%
See 1 more Smart Citation
“…Many wildlife species tend to avoid disturbances associated with roads such as moving vehicles, noise, and light (D'Amico et al, 2015;Denneboom et al, 2021). Although the carnivore species with the most crossings in our work are not particularly intolerant to human presence (Salgueiro et al, 2020), locations farthest from the paved roads are expected to still be areas where they forage and disperse the most across canals throughout their territory, increasing the likelihood of canal encounters and crossings. In the particular case of overpasses on irrigation canals, these generally connect unpaved roads used mainly by agricultural vehicles, implying little disturbance for these animals (Gačić et al, 2013).…”
Section: Primary Drivers Of Canal Crossings Through Overpassesmentioning
confidence: 92%
“…Importantly, vast irrigation systems can lead to overlooked yet marked land use changes (Gačić et al, and Petrovan 2019;Martinig and Mclaren, 2019). Among the animal groups, carnivore mammals, given their large home-ranges and dispersal needs (Salgueiro et al, 2020), have been well-suited to assess the effect of the different crossing structures at the landscape level (Clevenger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Not only plants, but also animal species may thrive in such degraded habitats. Rohrer et al (), Salgueiro et al (), and Martin‐Collado et al () studied the habitat preferences of two cliff‐nesting bird species—the Sand Martin ( Riparia riparia ) and the Black Redstart ( Phoenicurus ochruros )—and a semiaquatic mammal—the Eurasian otter ( Lutra lutra ). In the first two studies, both authors found that the species were attracted to mined areas especially when unsuitable conditions prevailed in surrounding matrix habitats.…”
Section: Quarries As Opportunities For Biodiversity and Ecosystem Sermentioning
confidence: 99%
“…Therefore, there is an urging need to employ effective restoration practices in post-extraction areas to accelerate ecosystem recovery (Salgueiro et al, 2020a). Traditionally, restoration practices largely relied on soil formation and revegetation, however, awareness on the restoration of ecological processes and the services they provide is currently increasing (e.g., Dmitrakova et al, 2018;Salgueiro et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Many plants often rely on seed dispersal services provided by frugivorous animals to colonise new areas (Herrera, 2002). Consequently, seed dispersal mediated by animals (i.e., zoochory) can contribute to further assist ecosystem restoration by promoting revegetation of vacant unrestored areas (Salgueiro et al, 2020b), if suitable conditions for their establishment are granted.…”
Section: Introductionmentioning
confidence: 99%